2022
DOI: 10.1007/s10639-022-10888-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ perceptions of technological pedagogical content knowledge in mainland China: A survey of teachers of Chinese as a second language

Abstract: There is an urgent need to address the critical demand for qualified Chinese language teachers against the background of China’s seeking greater Sino–foreign cultural and educational cooperation. The literature on integrating technological pedagogical content knowledge (TPACK) in language teaching has been increasing in the last few years. However, most of these studies focus on English language teachers. The objective of this study was to examine pre-service teachers’ understanding of TPACK for teaching Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The use of technology-based learning media can reduce students’ stress levels. Several studies have shown that using ICT in the classroom improves students’ soft skills [ 88 , 89 , 90 ]. However, teachers may need more time to understand students’ individual characters in order to provide appropriate support.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology-based learning media can reduce students’ stress levels. Several studies have shown that using ICT in the classroom improves students’ soft skills [ 88 , 89 , 90 ]. However, teachers may need more time to understand students’ individual characters in order to provide appropriate support.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, according to Pan et al (2021), the development of the human personality would be reliable and appropriate for the development of human values in society. It is critical to understand that the intention of the human being is based on different kinds of components and factors that are supporting it to modify the behavior for different actions (Qiu et al, 2022). However, it is up to the human being to get a different kind of intention and the factor behind the intention such as perceived norms that are regulating the human intention (Moin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also noted that the cultural dimensions and the perceived values are regulating the behavior of the people to the advanced level and developing their intention to do any kind of action (Ghufron & Ermawati, 2018). Significantly, in the light of the study of Qiu et al (2022), the people who have information about their normative beliefs and normative norms, they people are more attractive and more reliable to the opportunities for developing strategies and getting success.…”
Section: Literature Review 21 Innovative Machine Learning Behavior In...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is because the Chinese industry and government look more focused on the practical education of people to improve the industrial sector contributing to the economic performance of the country ( Zhang et al, 2019 ; Zhao et al, 2020 ). As a result of it, Chinese students lack the opportunity of getting an appropriate level of physical education because the education system is linked with the industry, and more practical teaching related to industrial growth and management is provided to the student ( Nazari and Alizadeh Oghyanous, 2022 ; Qiu et al, 2022 ; Zeng et al, 2022 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%